High-heat-resistance and high-transmittance substrate glass as well as preparation method and application thereof

By rationally preparing a variety of oxide components and preparing high heat-resistant and high-transmissive substrate glass, and forming a light absorption layer with blackening treatment, the heat resistance and adhesion problems in substrate glass thinning and ultra-thin glass processing are solved, and excellent comprehensive performance and wide application prospects are achieved.

CN119822635APending Publication Date: 2025-04-15CNBM PHOTONICS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510010767.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The prior art is difficult to thin the substrate glass while maintaining good performance. At the same time, the processing of ultra-thin glass requires high heat resistance, softening points and annealing points to ensure that the glass substrate does not deform during the thermal processing.

Method used

By reasonably preparing components such as SiO2, Al2O3, CaO, MgO, K2O, Na2O, Li2O, ZrO2, B2O3, Bi2O3, SnO2 and Sb2O3, substrate glass with high heat resistance and high transmission was prepared, and a light absorption layer was formed through blackening treatment to solve the problem of unstable adhesion.

Benefits of technology

It realizes the high transmittance, excellent heat resistance, high bending strength and good chemical stability of the substrate glass, and is suitable for the processing of high transmittance, high precision ultra-thin substrate glass and the application of digital product cover plates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822635A_ABST
    Figure CN119822635A_ABST
Patent Text Reader

Abstract

The invention relates to a special glass material, in particular to high-heat-resistance and high-transmittance substrate glass as well as a preparation method and application thereof. The high-temperature-resistant glass is prepared from the following components in percentage by weight: 58.0% to 65.0% of SiO2, 10.0% to 16.0% of Al2O3, 0.1% to 2.0% of CaO, 3.0% to 6.0% of MgO, 1.0% to 2.0% of K2O, 7.0% to 13.0% of Na2O, 0% to 2.0% of Li2O, 1.0% to 4.0% of ZrO2, 1.0% to 4.0% of B2O3, 0% to 3.0% of Bi2O3, 0% to 2.0% of SnO2 and 0% to 3.0% of Sb2O3. The substrate glass provided by the invention has good performance, not only can generate a black stray light eliminating layer in the aspects of strength, thermal stability, transmittance and chemical stability, but also can be applied to various high-transmittance and high-precision ultrathin substrate glass.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to special glass materials, in particular to substrate glass with high heat resistance and high transmittance, and a preparation method and application thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] In recent years, with the continuous improvement of people's living standards, electronic products have developed from the initial practicality to multifunctional, beautiful and lightweight. The thinning of substrate glass is now a trend recognized by the industry. The thinning of substrate glass can bring better optical quality, better glass touch and better user experience. However, how to thin the glass while maintaining good performance is the main problem at present, and the processing of ultra-thin glass is also a problem. Generally, higher heat resistance, higher softening point and annealing point are required to ensure that the glass substrate does not deform during the thermal processing process, while minimizing the dimensional deviation. Summary of the invention

[0004] In order to solve the shortcomings of the prior art, the purpose of the present invention is to provide a substrate glass with high heat resistance and high transmittance, and a preparation method and application thereof. The substrate glass provided by the present invention has good performance, not only in terms of strength, thermal stability, transmittance and chemical stability, but also the glass can produce a black stray light elimination layer under a reducing atmosphere, and the black matte layer can be processed and customized according to needs, overcoming the defects of the traditional substrate glass ink stray light elimination layer such as poor adhesion, and has good processing performance, and can be applied to various high-transmittance, high-precision ultra-thin substrate glasses.

[0005] In order to achieve the above object, the technical solution of the present invention is:

[0006] In the first aspect, a substrate glass with high heat resistance and high transmittance is composed of the following components by weight percentage: SiO 2 58.0~65.0%,Al 2 O 3 10.0~16.0%, CaO 0.1~2.0%, MgO 3.0~6.0%, K 2 O 1.0~2.0%, Na 2 O 7.0~13.0%, Li 2 O 0~2.0%, ZrO 2 1.0~4.0%, B 2 O 3 1.0~4.0%,Bi 2 O3 0~3.0%, SnO 2 0~2.0%, Sb 2 O 3 0~3.0%; among which, Bi 2 O 3 SnO 2 , Sb 2 O 3 The content of at most one component is 0.

[0007] In the present invention, the sum of the mass percentages of the various components is 100%.

[0008] In the above substrate glass system of the present invention, CaO, B 2 O 3 、MgO、SiO 2 SnO 2 and Sb 2 O 3 The integrated effect of CaO and B improves the thermal and chemical stability of the glass. At the same time, the addition of MgO further improves the corrosion resistance of the glass in complex environments and prolongs its service life. 2 O 3 and Sb 2 O 3 The synergistic effect of Na 2 O、SnO 2 、Bi 2 O 3 , B 2 O 3 and Sb 2 O 3 The combined effect of B reduces the difficulty of glass clarification and reduces defects such as bubbles in the glass melting process; among them, B 2 O 3 It can be used as a flux to accelerate the dissolution and clarification of glass and reduce the difficulty of glass molding; by controlling Al 2 O 3 The content of Al, MgO and CaO can reduce the crystallization tendency of glass and improve the transmittance of glass after forming; 2 O 3 ,MgO,B 2 O 3 , Li 2 O.Bi 2 O 3 , Sb 2 O 3 The introduction of Al improves the optical quality and enhances the optical transmittance of glass materials. 2 O 3, MgO and CaO content can reduce the tendency of glass crystallization and improve the permeability of glass after forming; by controlling the content of SnO 2 、Bi 2 O 3 and Sb 2 O 3 The content of can reduce the difficulty of glass clarification and reduce defects such as bubbles in the glass melting process. In addition, by controlling the reducing substance Bi 2 O 3 、Clarifying agent Sb 2 O 3 SnO 2 and alkali metal compounds K 2 O and Na 2 The content and proportion of O can further adjust the bending strength, optical properties, softening point, annealing point and strain point of the substrate glass.

[0009] In summary, the substrate glass provided by the present invention contains SiO 2 、Al 2 O 3 , CaO, MgO, K 2 O、Na 2 O. Li 2 O, ZrO 2 , B 2 O 3 、Bi 2 O 3 SnO 2 , Sb 2 O 3 , by precisely controlling the SiO 2 、Al 2 O 3 , CaO, MgO, K 2 O、Na 2 O. Li 2 O, ZrO 2 , B 2 O 3 、Bi 2 O 3 SnO 2 and Sb 2 O 3 These ingredients and their contents achieve excellent comprehensive properties, including thermal stability, strength and optical transmittance.

[0010] In a second aspect, a method for preparing the above-mentioned substrate glass with high heat resistance and high transmittance is provided, which comprises uniformly mixing the raw materials according to the proportion of each component, and then sequentially melting, stirring, clarifying and molding the mixture.

[0011] In a third aspect, an application of the above-mentioned substrate glass with high heat resistance and high transmittance in a screen panel.

[0012] Since the substrate glass provided by the present invention can form a light absorption layer on its surface after blackening treatment, thereby eliminating stray light, and has high acid resistance and moisture resistance stability, as well as excellent mechanical properties and processing properties, therefore, in a fourth aspect, a substrate glass with high heat resistance and high transmittance is used in a cover plate of a digital product.

[0013] The beneficial effects of the present invention are:

[0014] 1. The high heat-resistant and high-transmittance substrate glass provided by the present invention has a bending strength greater than 129MPa, a maximum optical transmittance of a 2mm glass sample greater than 91.3%, and a softening point

[0015] ≥915℃, annealing point ≥715℃, strain point ≥632℃, so it can be applied to the processing of various high-transmittance, high-precision ultra-thin substrate glasses.

[0016] 2. The high heat-resistant and high-transmittance substrate glass provided by the present invention has acid resistance and moisture resistance stability of level 1, good mechanical properties and processing properties, and can produce a light absorption layer after blackening and reduction, so that it can be used as the main material for various digital product cover plates. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0018] Figure 1 It is a comparative curve chart of the transmittance of the 2 mm thick glass products of Comparative Example 1 and Example 1 in the wavelength range of 500-1000 nm.

[0019] Figure 2 It is a comparison chart of the bending strength (a) and softening point (b) of the glass materials of Examples 1 to 9 and Comparative Examples 1 to 5. DETAILED DESCRIPTION

[0020] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0021] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0022] In view of the fact that the processing of ultra-thin glass requires higher heat resistance, higher softening point and annealing point to ensure that the glass substrate does not deform during the thermal processing while minimizing the dimensional deviation, the present invention proposes a substrate glass with high heat resistance and high transmittance, and its preparation method and application.

[0023] A typical embodiment of the present invention provides a substrate glass with high heat resistance and high transmittance, which is composed of the following components by weight percentage: SiO 2 58.0~65.0%,Al 2 O 3 10.0~16.0%, CaO0.1~2.0%, MgO3.0~6.0%, K 2 O 1.0~2.0%, Na 2 O 7.0~13.0%, Li 2 O 0~2.0%, ZrO 2 1.0~4.0%, B 2 O 3 1.0~4.0%,Bi 2 O 3 0~3.0%, SnO 2 0~2.0%, Sb 2 O 3 0~3.0%; among which, Bi 2 O 3 SnO 2 , Sb 2 O 3 The content of at most one component is 0.

[0024] In the present invention, SiO 2 It is a glass-forming oxide. As the main component of glass, it provides the basic framework of the structure and gives the glass good chemical stability and mechanical strength. 2 The content can reduce the thermal expansion coefficient of glass and improve the thermal stability, chemical stability, softening temperature, heat resistance, hardness and mechanical strength of glass. 2 Too high a content of SiO may result in an increase in melting point and difficulty in processing; 2 Too low a content of SiO will weaken the chemical stability and mechanical strength of the glass.2 Preferably, it is 58 to 63%, 59.7 to 63%, 61 to 63%, 61.5 to 62.5%, etc.

[0025] Al 2 O 3 It is an essential component to improve the chemical stability of glass, which can reduce the tendency of glass crystallization. It is also a component to increase the hardness and mechanical strength of glass and increase the tensile elastic modulus. In the glass network structure, aluminum oxide is a network intermediate oxide, between the network generator and the network exogenous body. 2 O 3 Preferably, it is 11 to 16%, 11.5 to 16%, 12 to 16%, 13 to 16%, 13 to 15%, 13.5 to 14.5% or the like.

[0026] In the present invention, the introduction of CaO can increase the chemical stability and mechanical strength of the glass, but when the amount introduced is too much, it is easy to cause the glass to crystallize and reduce the thermal stability of the glass. At the same time, CaO can reduce the viscosity of the glass at high temperature, which is conducive to clarification; the introduction of MgO can improve the thermal stability of the glass, and the introduction of MgO will reduce the thermal expansion coefficient of the glass, but too much MgO will increase the viscosity of the glass, making it difficult to form the glass. MgO and CaO together enhance the mechanical strength and chemical durability of the glass in the present invention. The addition of MgO is particularly helpful to reduce the increase in the thermal expansion coefficient caused by CaO. MgO is preferably 3.0-5.0%, 3.0-4.5%, 3.0-4.0%, etc. CaO is preferably 0.1-1.5%, 0.5-1.5%, 0.8-1.2%, etc.

[0027] In the present invention, K 2 O and Na 2 O is the network outer oxide of glass. Alkali metal ions are easy to move and diffuse in the glass, which can reduce the viscosity of glass at high temperature melting and make the glass easy to melt. It is a good flux, but the amount introduced should not be too much. Too much introduction will increase the thermal expansion coefficient of glass and reduce the chemical stability, thermal stability and mechanical strength of glass. In addition, Na in glass + Chemical strengthening is also called ion exchange strengthening. Its principle is to place the glass in molten potassium nitrate at a certain temperature to make the small radius ions (such as Na + ) and large radius ions in molten salts (such as K + ) are replaced, thus producing a "squeezing" effect on the glass surface, forming a surface compressive stress layer, and improving the mechanical strength of the glass material. 2 O is preferably 1.5 to 2.0%, 1.8 to 2.0%, etc. 2O is preferably 8.0 to 13.0%, 8.0 to 11.0%, 9.0 to 11.0%, 9.5 to 10.5%, etc.

[0028] In the present invention, Li 2 O can combine with oxygen atoms in the glass network to form Li-O bonds, which helps to strengthen the network structure of the glass and improve the physical properties of the glass. 2 The introduction of O can reduce the tendency of glass to form crystals during cooling and solidification, help maintain the amorphous state of glass, and improve the optical transparency of glass, thereby making glass easier to be transparent, improving the optical transmittance of glass, and reducing the haze of glass. However, it should be noted that Li 2 The amount of O used needs to be precisely controlled. Excess Li 2 O will reduce the chemical stability of the glass and may cause the glass to be more susceptible to crystallization and phase separation. 2 O is preferably 0 to 1.5%, 0.1 to 1.5%, 0.1 to 1.0%, 0.2 to 0.8%, etc.

[0029] In the present invention, ZrO 2 It is a glass intermediate oxide that improves chemical stability and prevents the exposure of alkali metal and alkaline earth metal ions. It is also an important component for improving the tensile elastic modulus and is very helpful for improving the hardness of glass after chemical strengthening. 2 Preferably, it is 1.0 to 3.5%, 1.0 to 3.0%, 1.5 to 2.5%, etc.

[0030] In the present invention, B 2 O 3 It is also a glass-forming oxide, which is a triangular boron oxide [BO 3 ] and boron-oxygen tetrahedron [BO 4 ] is a structural unit, which forms a structural network with silicate tetrahedron in borosilicate glass. 2 O 3 At high temperatures, it can reduce the viscosity of the glass, and at low temperatures, it can increase the viscosity of the glass, so B 2 O 3 Glass with a higher content has a wider forming temperature range. 2 O 3 It also plays a role in fluxing, accelerating the dissolution and clarification of glass. 2 O 3 When the amount added is too high, the expansion coefficient of the glass will increase due to the increase of boron-oxygen triangles, resulting in boron anomaly and reducing the chemical stability of the glass. 2 O 3 Preferably, it is 1.0 to 3.5%, 2.5 to 3.5%, 2.8 to 3.2%, etc.

[0031] In the present invention, the synergistic effect of two or three factors can improve the light absorption rate of the glass after reduction and blackening. 2 O 3 The addition of Bi can improve the refractive index and dispersion ability. 2 O 3 It also helps to improve the thermal stability of glass and enhance its light absorption capacity. 2 O 3 or Bi(NO 3 ) 3 Introduced) can be reduced to black in a high temperature hydrogen atmosphere, this property can be used to optimize the stray light absorption effect. 2 O 3 The introduction of Bi needs to be precisely controlled. 2 O 3 This may lead to a significant decrease in the chemical stability of the glass, especially when reacting with reducing gases. 2 O 3 In the glass melting process, it may cause serious corrosion to the melting container, which limits its application in glass production. In addition, too much Bi 2 O 3 It may also promote the crystallization of glass, affecting its transparency and optical uniformity. 2 O 3 If the content is insufficient, it is difficult to improve the optical properties. 2 The introduction of SnO can enhance the transparency and heat resistance of glass. At the same time, during the melting process of glass, 2 It will react with other glass components to form hard crystals. These crystals are dispersed in the glass, which can increase the hardness and flexural strength of the glass and reduce the possibility of scratches on the glass surface. 2 O 3 It can be used as an additive for glass liquid to improve the heat resistance, impact resistance, transparency and other properties of glass. It can also reduce the thermal expansion coefficient of glass, making the products made of glass liquid more tough and transparent. 2 and Sb 2 O 3 It can be used as a clarifying agent to reduce the difficulty of clarifying glass. 2 O 3 Preferably, it is 0 to 2.0%, 0.5 to 2.0%, 0.5 to 1.5%, 0.8 to 1.2%, etc. SnO 2 Preferably, it is 0 to 1.5%, 0.1 to 1.5%, 0.1 to 1.0%, 0.2 to 0.8%, etc. Sb 2 O 3Preferred are 0.1 to 3.0%, 0.1 to 2.0%, 0.1 to 1.5%, 0.5 to 1.5%, 0.5 to 1.2%, 0.8 to 1.2%, 0.8 to 1.1% and the like.

[0032] In some embodiments, SiO 2 58.0~65.0%,Al 2 O 3 10.0~16.0%, CaO 0.1~2.0%, MgO3.0~6.0%, K 2 O 1.0~2.0%, Na 2 O 7.0~13.0%, Li 2 O 0~2.0%, ZrO 2 1.0~4.0%, B 2 O 3 1.0~4.0%,Bi 2 O 3 0~2.0%, SnO 2 0~2.0%, Sb 2 O 3 0~3.0%.

[0033] In some embodiments, Na 2 The content of O is greater than two-seven times that of K 2 O content. Studies have shown that glass with this component has better performance.

[0034] In some embodiments, B 2 O 3 The content is less than two-fifths of Al 2 O 3 Research shows that glass with this component has better performance.

[0035] In some embodiments, the bending strength is not less than 129 MPa, preferably 129-148 MPa, and further preferably 140-148 MPa.

[0036] In some embodiments, the maximum optical transmittance of a 2 mm glass sample is not less than 91.3%, preferably 91.3-92.9%, and more preferably 91.6-92.9%.

[0037] In some embodiments, the softening point is ≥ 915°C, preferably 915-945°C, and more preferably 933-945°C.

[0038] In some embodiments, the annealing point is ≥715°C, preferably 715-731°C, and more preferably 724-731°C.

[0039] In some embodiments, the strain point is ≥ 632°C, preferably 632-671°C, and more preferably 658-671°C.

[0040] Another embodiment of the present invention provides a method for preparing the above-mentioned substrate glass with high heat resistance and high transmittance, comprising uniformly mixing the raw materials according to the proportion of each component, and then sequentially melting, stirring, clarifying and molding the mixture to obtain the glass.

[0041] In some embodiments, the melting temperature is 1500-1580° C. Specifically, the melting time is 8-30 hours. Under this melting time, it is helpful to clarify the glass liquid.

[0042] When the uniformity of the liquid before glass forming is low, the liquid is prone to stratification or agglomeration, making it difficult to melt and homogenize the glass, and even causing streaks or stone defects. Therefore, the glass liquid before forming needs to be stirred. In some embodiments, the stirring speed is 10 to 20 r / min, and the stirring time is 3 to 12 hours. This stirring condition is conducive to improving the uniformity of the liquid of the glass system.

[0043] In some embodiments, the molding temperature is 1350-1400° C., and the molding time is 5-25 minutes. Such molding conditions are conducive to rapid molding of glass and avoid the generation of secondary bubbles and impurities.

[0044] A third embodiment of the present invention provides an application of the above-mentioned substrate glass with high heat resistance and high transmittance in a screen panel.

[0045] A fourth embodiment of the present invention provides an application of the above-mentioned substrate glass with high heat resistance and high transmittance in a cover plate of a digital product.

[0046] In some embodiments, the substrate glass with high heat resistance and high transmittance includes a light absorption region, and the maximum optical transmittance of the light absorption region is not higher than 2.9%, preferably 1.3-2.9%, and more preferably 1.3-1.7%.

[0047] In one or more embodiments, the light absorption area is obtained by blackening the substrate glass with high heat resistance and high transmittance. Specifically, annealing is performed first, and then blackening treatment is performed. Annealing can eliminate the internal stress of the glass, thereby meeting the requirements of later cold processing. More specifically, the annealing temperature is 500-550°C. More specifically, the blackening treatment is carried out in a reducing atmosphere, the blackening treatment time is 4000-16000min, the pressure is 0.01-0.5MPa, and the temperature is 450-620°C. For example, in a reducing atmosphere with a pressure of 0.01MPa, it is heated to 600°C and the blackening treatment is 10000min. More specifically, the reduction treatment is carried out in a hydrogen atmosphere, and there are multiple cycles of inflation and deflation during the entire reduction process, and a cycle period is 160-300min.

[0048] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in combination with specific embodiments and comparative examples.

[0049] The performance parameters in the following embodiments are measured according to the following methods:

[0050] The thermal expansion coefficient α of the glass sample was tested using the DIL 402 expansion coefficient tester produced by NETZSCH, Germany. Sample preparation: The glass sample was polished into a cylindrical glass strip of Φ6×50mm, and the two end surfaces were parallel. The heating rate was set to 5℃ / min, and the data acquisition cycle was 20ms. Refer to GB / T7962.16~2010.

[0051] The softening point temperature of the glass sample is tested using the Model PPV-1000 / 1200 plate viscometer produced by Orton. Sample preparation: The glass sample is polished into a cylindrical glass strip of Φ6×6mm, and the two end faces are parallel. The sample is placed between the top and bottom discs, which are made of heat-resistant metal alloys with a diameter of 44mm and a thickness of 6mm. The top metal disc is connected to the bottom of the probe rod. Two very thin platinum films (40mm in diameter and 0.001 inches thick) are placed between the sample and the top and bottom discs to facilitate sampling and sample placement. Refer to ASTM C-1351M.

[0052] The transmittance test was carried out using a UV-visible-infrared spectrophotometer.

[0053] After the surface of the polished glass sample is corroded by the test medium with acidity of pH2.9, pH4.6, and pH6.0, observe the time when the purple-blue interference color appears on the glass surface, or the surface becomes mottled or falls off under an incandescent lamp. The acid resistance stability of colorless optical glass is classified in descending order according to the length of time. Refer to GB / T 7962.14~2010.

[0054] Polished glass samples are kept at a constant temperature and humidity of 50°C and 85% relative humidity for 20 hours, and the moisture resistance stability of colorless optical glass is classified in descending order by comparing the turbidity values ​​with those of standard samples H (BaK7) and H (ZK9). Refer to GB / T7962.15~2010.

[0055] The bending strength of glass samples is tested using the three-point bending method. The glass sample is processed into the required size for the test, and then the glass sample is placed between two supporting points and a fixed load is applied perpendicular to the center of the sample. Then, by applying different bending moments, the bending stress and strain of the glass are measured under different conditions. Finally, the bending strength of the glass is determined. Refer to GB / T 37781-2019.

[0056] Example 1

[0057] The components of the high heat-resistant and high-transmittance substrate glass of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Table 1, Table 3, Figures 1-2 .

[0058] The preparation method of high heat-resistant and high-transmittance substrate glass is as follows: quartz sand, aluminum hydroxide, calcium carbonate, basic magnesium carbonate, potassium nitrate, sodium nitrate, lithium carbonate, zirconium oxide, boric acid, bismuth oxide, tin oxide and antimony oxide are used as raw materials, and after being fully mixed, they are melted at 1500°C for 8 hours, mechanically stirred (10r / min, 3 hours), assisted with high-temperature clarification, and pressed at 1350°C (molding time is 5 minutes) to obtain glass blanks. The glass blanks are placed in an annealing furnace heated to 520°C in advance for annealing to eliminate the stress in the glass to meet the requirements of later cold processing.

[0059] After annealing, the glass blank is processed into a certain size and placed in a blackening reduction furnace. The blackening program is set, the blackening temperature is 600°C, the reducing gas hydrogen pressure is 0.01MPa, and the blackening time is 10000min. After the blackening treatment is completed, a stray light absorption layer is formed on the glass surface.

[0060] Example 2

[0061] The components of the high heat-resistant and high-transmittance substrate glass of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Table 1, Table 3, Figure 2 .

[0062] In the preparation method of high heat-resistant and high-transmittance substrate glass, the melting temperature is 1550°C and the melting time is 16 hours; mechanical stirring (20r / min, 12 hours), the molding temperature is 1400°C, and the molding time is 15 minutes. The other preparation steps and parameters are the same as those in Example 1.

[0063] After annealing, the glass blank is processed into a certain size and placed in a blackening reduction furnace. The blackening program is set to a blackening temperature of 620°C, a reducing gas hydrogen pressure of 0.2MPa, and a blackening time of 10,000 minutes. After the blackening process is completed, a stray light absorption layer is formed on the glass surface.

[0064] Example 3

[0065] The components of the high heat-resistant and high-transmittance substrate glass of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Table 1, Table 3, Figure 2 .

[0066] In the preparation method of high heat-resistant and high-transmittance substrate glass in this embodiment, the melting temperature is 1580°C and the melting time is 30h; mechanical stirring (20r / min, 12h), the molding temperature is 1400°C, and the molding time is 25min. The other preparation steps and parameters are the same as those in Example 1.

[0067] After annealing, the glass blank is processed into a certain size and placed in a blackening reduction furnace. The blackening program is set to a blackening temperature of 450°C, a reducing gas hydrogen pressure of 0.3MPa, and a blackening time of 4000min. After the blackening process is completed, a stray light absorption layer is formed on the glass surface.

[0068] Example 4

[0069] The components of the high heat-resistant and high-transmittance substrate glass of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Table 1, Table 3, Figure 2 .

[0070] In the preparation method of high heat-resistant and high-transmittance substrate glass in this embodiment, the melting temperature is 1560°C and the melting time is 20h; mechanical stirring (20r / min, 14h), the molding temperature is 1400°C, and the molding time is 25min. The other preparation steps and parameters are the same as those in Example 1.

[0071] After annealing, the glass blank is processed into a certain size and placed in a blackening reduction furnace. The blackening program is set with a blackening temperature of 500°C, a reducing gas hydrogen pressure of 0.4MPa, and a blackening time of 6000min. After the blackening treatment is completed, a stray light absorption layer is formed on the glass surface.

[0072] Example 5

[0073] The components of the high heat-resistant and high-transmittance substrate glass of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Table 1, Table 3, Figure 2 .

[0074] In the preparation method of high heat-resistant and high-transmittance substrate glass in this embodiment, the melting temperature is 1520°C and the melting time is 25h; mechanical stirring (20r / min, 14h), the molding temperature is 1380°C, and the molding time is 25min. The other preparation steps and parameters are the same as those in Example 1.

[0075] After annealing, the glass blank is processed into a certain size and placed in a blackening reduction furnace. The blackening program is set to a blackening temperature of 530°C, a reducing gas hydrogen pressure of 0.5MPa, and a blackening time of 12000min. After the blackening treatment is completed, a stray light absorption layer is formed on the glass surface.

[0076] Example 6

[0077] The components of the high heat-resistant and high-transmittance substrate glass of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Table 1, Table 3, Figure 2 .

[0078] In the preparation method of high heat-resistant and high-transmittance substrate glass in this embodiment, the melting temperature is 1560°C and the melting time is 30h; mechanical stirring (20r / min, 12h), the molding temperature is 1400°C, and the molding time is 25min. The other preparation steps and parameters are the same as those in Example 1.

[0079] After annealing, the glass blank is processed into a certain size and placed in a blackening reduction furnace. The blackening program is set to a blackening temperature of 620°C, a reducing gas hydrogen pressure of 0.2MPa, and a blackening time of 16000min. After the blackening treatment is completed, a stray light absorption layer is formed on the glass surface.

[0080] Example 7

[0081] The components of the high heat-resistant and high-transmittance substrate glass of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Table 1, Table 3, Figure 2 .

[0082] In the preparation method of high heat-resistant and high-transmittance substrate glass in this embodiment, the melting temperature is 1550°C and the melting time is 30h; mechanical stirring (20r / min, 14h), the molding temperature is 1400°C, and the molding time is 25min. The other preparation steps and parameters are the same as those in Example 1.

[0083] After annealing, the glass blank is processed into a certain size and placed in a blackening reduction furnace. The blackening program is set to a blackening temperature of 600°C, a reducing gas hydrogen pressure of 0.2MPa, and a blackening time of 13000min. After the blackening treatment is completed, a stray light absorption layer is formed on the glass surface.

[0084] Example 8

[0085] The components of the high heat-resistant and high-transmittance substrate glass of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Table 1, Table 3, Figure 2 .

[0086] In the preparation method of high heat-resistant and high-transmittance substrate glass in this embodiment, the melting temperature is 1550°C and the melting time is 30h; mechanical stirring (20r / min, 14h), the molding temperature is 1400°C, and the molding time is 20min. The other preparation steps and parameters are the same as those in Example 1.

[0087] After annealing, the glass blank is processed into a certain size and placed in a blackening reduction furnace. The blackening program is set to a blackening temperature of 610°C, a reducing gas hydrogen pressure of 0.2MPa, and a blackening time of 8000min. After the blackening process is completed, a stray light absorption layer is formed on the glass surface.

[0088] Example 9

[0089] The components of the high heat-resistant and high-transmittance substrate glass of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Table 1, Table 3, Figure 2 .

[0090] In the preparation method of high heat-resistant and high-transmittance substrate glass in this embodiment, the melting temperature is 1560°C and the melting time is 30h; mechanical stirring (20r / min, 14h), the molding temperature is 1400°C, and the molding time is 20min. The other preparation steps and parameters are the same as those in Example 1.

[0091] After annealing, the glass blank is processed into a certain size and placed in a blackening reduction furnace. The blackening program is set to a blackening temperature of 590°C, a reducing gas hydrogen pressure of 0.2MPa, and a blackening time of 9000min. After the blackening treatment is completed, a stray light absorption layer is formed on the glass surface.

[0092] Comparative Examples 1 to 5

[0093] The components of the glasses of Comparative Examples 1 to 5, the weight percentage of each component, and the physical properties of the glasses obtained are shown in Tables 2, 4, Figures 1-2 .

[0094] The preparation steps, blackening reduction steps and parameters of the glass in Comparative Examples 1 to 5 are the same as those in Example 2.

[0095] Table 1 Components and contents of high heat-resistant and high-transmittance substrate glass in Examples 1 to 9 of the present invention

[0096]

[0097] Table 2 Components and contents of glass in comparative examples 1-5 of the present invention

[0098]

[0099]

[0100] Table 3 Performance test results of glass samples of Examples 1 to 9

[0101]

[0102]

[0103] Table 4 Performance test results of glass samples of Comparative Examples 1 to 5

[0104]

[0105]

[0106] In Tables 3 and 4, except for the maximum optical transmittance after reduction, all data were tested using the glass samples before reduction.

[0107] By reasonably adding corresponding components and controlling the ratio of each component in the raw materials, the optical transmittance, bending strength, heat resistance and acid and alkali corrosion resistance of the glass in Examples 1 to 9 are better. As can be seen from Table 3, the optical transmittance of the high heat-resistant and high-transmittance substrate glass prepared in Examples 1 to 9 of the present invention is as follows: within the wavelength range of 500 to 1000 nm, the maximum transmittance is ≥ 91.3%. The comprehensive performance is better than the glass involved in Comparative Examples 1 to 5, and the good acid / moisture resistance stability can maintain the stability of the internal structure of the glass for a long time.

[0108] As can be seen from the above, the high heat-resistant and high transmittance substrate glass provided by Examples 1 to 9 of the present invention has excellent optical transmittance, heat resistance, high bending strength and good chemical stability. This is because in Examples 1 to 9 of the present invention, the proportion of each component raw material is adjusted in the preparation of the high heat-resistant and high transmittance substrate glass, and a suitable stirring speed and time are set. Therefore, the high heat-resistant and high transmittance substrate glass of the present invention has excellent optical transmittance, heat resistance, high bending strength and good chemical stability, and has broad application prospects.

[0109] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A glass substrate having high heat resistance and high transmittance, characterized in that: Calculated by mass percentage, it is composed of the following components: SiO2 58.0-65.0%, Al2O3 10.0-16.0%, CaO 0.1-2.0%, MgO 3.0-6.0%, K2O 1.0-2.0%, Na2O 7.0-13.0%, Li2O 0-2.0%, ZrO2 1.0-4.0%, B2O3 1.0-4.0%, Bi2O3 0-3.0%, SnO2 0-2.0%, Sb2O3 0-3.0%; among which, the content of at most one of Bi2O3, SnO2 and Sb2O3 is 0.

2. The high heat-resistant and high-transmittance substrate glass according to claim 1, characterized in that: SiO2 is 58-63%, or 59.7-63%, or 61-63%, or 61.5-62.5%; Or, Al2O3 is 11-16%, or 11.5-16%, or 12-16%, or 13-16%, or 13-15%, or 13.5-14.5%; Or, MgO is 3.0-5.0%, or 3.0-4.5%, or 3.0-4.0%; Or, CaO is 0.1-1.5%, or 0.5-1.5%, or 0.8-1.2%; Or, K2O is 1.5-2.0%, or 1.8-2.0%; Or, Na2O is 8.0-13.0%, or 8.0-11.0%, or 9.0-11.0%, or 9.5-10.5%; Or, Li2O is 0-1.5%, or 0.1-1.5%, or 0.1-1.0%, or 0.2-0.8%; Or, ZrO2 is 1.0-3.5%, or 1.0-3.0%, or 1.5-2.5%; Or, B2O3 is 1.0-3.5%, or 2.5-3.5%, or 2.8-3.2%; Or, Bi2O3 is 0-2.0%, or 0.5-2.0%, or 0.5-1.5%, or 0.8-1.2%; Or, SnO2 is 0-1.5%, or 0.1-1.5%, or 0.1-1.0%, or 0.2-0.8%; Or, Sb2O3 is 0.1-3.0%, or 0.1-2.0%, or 0.1-1.5%, or 0.5-1.5%, or 0.5-1.2%, or 0.8-1.2%, or 0.8-1.1%; Or, SiO2 58.0~65.0%, Al2O3 10.0~16.0%, CaO 0.1~2.0%, MgO 3.0~6.0%, K2O1.0~2.0%, Na2O 7.0~13.0%, Li2O 0~2.0%, ZrO2 1.0~4.0%, B2O3 1.0~4.0%, Bi2O30~2.0%, SnO2 0~2.0%, Sb2O3 0~3.0%.

3. The high heat-resistant and high-transmittance substrate glass according to claim 1, wherein Na The content of 2O is greater than two-seven times the content of K2O; Or, the content of B2O3 is less than two-fifths of the content of Al2O3.

4. The high heat-resistant and high-transmittance substrate glass according to claim 1, characterized in that: The flexural strength is not less than 129 MPa, preferably 129 to 148 MPa, and more preferably 140 to 148 MPa; Or, the maximum optical transmittance of a 2 mm glass sample is not less than 91.3%, preferably 91.3 to 92.9%, and more preferably 91.6 to 92.9%; Or, the softening point is ≥ 915°C, preferably 915 to 945°C, and more preferably 933 to 945°C; In some embodiments, the annealing point is ≥715°C, preferably 715-731°C, and further preferably 724-731°C; Alternatively, the strain point is ≥ 632°C, preferably 632 to 671°C, and more preferably 658 to 671°C.

5. A method for preparing a substrate glass with high heat resistance and high transmittance as claimed in claim 1, characterized in that: The raw materials are uniformly mixed according to the proportion of each component, and then the mixture is melted, stirred, clarified and formed in sequence to obtain the product.

6. The method for preparing a substrate glass with high heat resistance and high transmittance as claimed in claim 5, characterized in that: The melting temperature is 1500-1580°C; preferably, the melting time is 8-30h; Or, the stirring speed is 10-20 r / min, and the stirring time is 3-12 h; Alternatively, the molding temperature is 1350-1400° C., and the molding time is 5-25 min.

7. Use of the high heat-resistant and high-transmittance substrate glass according to any one of claims 1 to 4 in a screen panel.

8. Use of the high heat-resistant and high-transmittance substrate glass according to any one of claims 1 to 4 in a cover plate of a digital product.

9. The use according to claim 8, characterized in that: The substrate glass with high heat resistance and high transmittance includes a light absorption region, and the maximum optical transmittance of the light absorption region is not higher than 2.9%, preferably 1.3-2.9%, and more preferably 1.3-1.7%.

10. The use according to claim 9, characterized in that: The light absorption region is obtained by blackening the substrate glass with high heat resistance and high transmittance; preferably, annealing is performed first and then blackening is performed; preferably, the annealing temperature is 500-550°C; preferably, the blackening treatment is performed in a reducing atmosphere, the blackening treatment time is 4000-16000 min, the pressure is 0.01-0.5 MPa, and the temperature is 450-620°C.